Agricultural finance from crops to land, water and infrastructure - Geman, Helyette (The Wiley finance series., 2015)
"Agricultural Finance is the only book which comprehensively deals with worldwide agriculture markets, spikes in agricultural commodity prices, trading strategies (CTAs and others), the agribusiness industry, the challenges of feeding the planet as well as the fascinating subjects of land, water, fertilizers, biofuels and ethanol. Given their importance to human life, cycles in agricultural commodity prices are very different from the likes of copper or crude oil.With over 15 chapters the book will feature topics such as agricultural insurance, energy, shipping and bunker prices, sustainability, ethanol, water, investments in land, fertilizers, soft commodities such as sugar, coffee ; rubber; agricultural policies, subsidies, econometrics and agricultural derivatives and farming risk-management.Contents will also include chapters on:1."Futures, options on Agricultural Commodities and Risk-Management in Farming and Agribusiness"2. Real Options in Land and Valuation of Physical Assets, Crushers and Storage Facilities 3. Structured Products and ETFs on Agricultural Commodities4. Trade Finance in an Era of Credit Shortage5. Securitization and Commodity- Linked Notes6 Grains (wheat, corn, soybeans)7 Softs: Coffee, Cocoa, Cotton8. Shipping as a Key component of Agricultural trade; the Major Routes and the Costs"--Provided by publisher.